AREA NAVIGATION AND POSSIBILITIES OF ITS APPLICATION IN THE AIRSPACE OF THE REPUBLIC OF UZBEKISTAN - D. E. Eshmuradov; M. V. Mikryukov; M. A. Mavlyanova (Научный вестник МГТУ ГА)
The article describes the concept of area navigation, its application in practice, as well as the advantages of area navigation over traditional. The introduction of area navigation in the airspace of the Republic of Uzbekistan will increase its capacity, reduce the workload of air traffic controllers, as well as increase the amount of aeronautical charges for foreign aircrafts. The project of the use of area navigation in the Republic of Uzbekistan is in the stage of analysis and development, but its advantages are obvious. Only one air route is being considered currently.